Expression profiles and genomic organisation of group A protein phosphatase 2C genes in Brassica oleracea. (11th June 2013) - Ludwików, A.; Babula‐Skowrońska, D.; Szczepaniak, M.; Belter, N.; Dominiak, E.; Sadowski, J.
Abstract We investigated the expression profiles and genomic organisation of the ABA‐responsive genes encoding protein phosphatases 2C (PP2C, group A members) in Brassica oleracea to better understand their functional and genetic relations. Gene expression profiling of drought responsive genes in B. oleracea and Arabidopsis thaliana revealed significant differences in the gene expression pattern of a key regulator of ABA signalling—ABI1 PP2C. This finding prompted us to study genetic relations within the PP2Cs group A in the Brassica species. Twenty homologous B. oleracea sequences were identified and characterised as putative PP2C group A members. Phylogenetic analysis revealed that the B. oleracea homologues were closely related to the particular members of the A. thaliana PP2C. The genetic analysis corroborated the presence of two to three gene copies in B. oleracea in comparison to the nine unique PP2C genes in the A. thaliana genome. Gene expression analyses showed significant differences in PP2C gene expression pattern in B. oleracea. Our results indicate that PP2C‐based drought stress signalling in B. oleracea has evolved distinctly. Different reactions of particular B. oleracea PP2C genes to drought stress and ABA treatment indicate low conservation of gene expression patterns and functional divergence between B. oleracea and A. thaliana homologous genes.